Nanoparticle-based approaches for treating restenosis after vascular injury - Zhao, Liangfeng; Feng, Liuliu; Shan, Rong; Huang, Yue; Shen, Li; Fan, Mingliang; Wang, Yu (Frontiers in Pharmacology, 2024)
Percutaneous coronary intervention (PCI) is currently the main method for treating coronary artery stenosis, but the incidence of restenosis after PCI is relatively high. Restenosis, the narrowing of blood vessels by more than 50% of the normal diameter after PCI, severely compromises the therapeutic efficacy. Therefore, preventing postinterventional restenosis is important. Vascular restenosis is mainly associated with endothelial injury, the inflammatory response, the proliferation and migration of vascular smooth muscle cells (VSMCs), excessive deposition of extracellular matrix (ECM) and intimal hyperplasia (IH) and is usually prevented by administering antiproliferative or antiinflammatory drugs through drug-eluting stents (DESs); however, DESs can lead to uncontrolled drug release. In addition, as extracorporeal implants, they can cause inflammation and thrombosis, resulting in suboptimal treatment. Therefore, there is an urgent need for a drug carrier with controlled drug release and high biocompatibility for in vivo drug delivery to prevent restenosis. The development of nanotechnology has enabled the preparation of nanoparticle drug carriers with low toxicity, high drug loading, high biocompatibility, precise targeting, controlled drug release and excellent intracellular delivery ability. This review summarizes the advantages of nanoparticle drug carriers for treating vascular restenosis, as well as how nanoparticles have improved targeting, slowed the release of therapeutic agents, and prolonged circulation in vivo to prevent vascular restenosis more effectively. The overall purpose of this review is to present an overview of nanoparticle therapy for vascular restenosis. We expect these findings to provide insight into nanoparticle-based therapeutic approaches for vascular restenosis.